Variation in Macro and Trace Elements in Progression of Type 2 Diabetes - Khalid Siddiqui; Nahla Bawazeer; Salini Scaria Joy (The Scientific World Journal)
Macro elements are the minerals of which the body needs more amounts and are more important than any other elements. Trace elements constitute a minute part of the living tissues and have various metabolic characteristics and functions. Trace elements participate in tissue and cellular and subcellular functions; these include immune regulation by humoral and cellular mechanisms, nerve conduction, muscle contractions, membrane potential regulations, and mitochondrial activity and enzyme reactions. The status of micronutrients such as iron and vanadium is higher in type 2 diabetes. The calcium, magnesium, sodium, chromium, cobalt, iodine, iron, selenium, manganese, and zinc seem to be low in type 2 diabetes while elements such as potassium and copper have no effect. In this review, we emphasized the status of macro and trace elements in type 2 diabetes and its advantages or disadvantages; this helps to understand the mechanism, progression, and prevention of type 2 diabetes due to the lack and deficiency of different macro and trace elements.